Optimalisasi Peran Reservation Section Pada Proses Pemesanan Kamar Hotel (Studi Kasus Hotel D’cokro Yogyakarta) - M. Shodiq Bimo Sakti1; Atun Yulianto - AKPAR BSI Yogyakarta (Universitas Bina Sarana Informatika, 2012)
ABSTRACT - D'Cokro Hotel Yogyakarta is a company engaged in accommodation services, which requires the existence of an understanding of how to handle a room bookings to give more satisfaction to the guests. In order for a room booking service can be carried out effectively, accurately and quickly.One aim of this study is to know the reservation staff in an effort to meet guest's wishes when booking a room. The approach to research method used is descriptive qualitative research approach. This study provides an overview of the task part of the reservation section in serving guests. Findings arising problems are discussed in this section are qualitatively through reference library. Data collected through observation, interviews, library research and documentation.The results of this study indicate that atitue or hospitality on the responsibility given to the section of the reservation are the key to success in serving guests D'Cokro. The application of information technology in booking a room through this section can help employees serve guests quickly, accurately and more efficiently than in the service book manually.Keywords : Optimalization, Reservation Section, Hotel Reservation